Analisis Perilaku dan Preferensi Mahasiswa dalam Aktivitas Belanja Online di Era Digital - Rahmah, Baiq Ziadatu; Rizkika, Alya; Madiyawati, Cici; Gunawan, Gunawan (Indonesian Publication Center, 2026)
This study aims to analyze the behavior and preferences of college students in online shopping activities in the digital era. Technological developments, internet usage, and easy access to e-commerce have shaped new consumption patterns among college students. This study used a quantitative descriptive method with data collection through an online survey involving 69 students from 10 study programs at the Faculty of Teacher Training and Education, University of Mataram. Data were analyzed using descriptive statistics to examine trends in shopping frequency, platform preferences, product types, payment methods, and the influence of social media. The results showed that most students rarely shop online (44.9%), with Shopee as the most widely used platform (81.2%). The most dominant type of product purchased was clothing and accessories (87%). The main reasons for online shopping include convenience (43.5%), numerous promotions/discounts, and lower prices. Cash on Delivery (COD) was the most frequently used payment method (63.8%), indicating a need for security during transactions. In addition, 66.7% of respondents admitted to experiencing disappointment, especially because the product did not meet expectations. The average perception score showed that students viewed online shopping as efficient, but still considered product risks and shipping costs. Overall, students' online shopping behavior is influenced by convenience, product completeness, promotions, and level of trust in sellers.